Sustainable Landuse Model at Upper Cikapundung River â North Bandung - Darsiharjo, Darsiharjo (Forum Geografi, 2004)
Land use in upper catchment of Cikapundung progressively do not in control, so that many land use disagree with required condition. The objectives of the research were to: 1) evaluating of existing land use suitability with to its land suitability; and 2) compiling simulation land use model which have been formulated to study the expense of conservation, beneficial crop type and conservation action alternative. In this research made three submodel (erosion submodel use USLE and Arsyad, runoff submodel use Bransby and Williams, and social economic submodel use B/C ratio and NPV); and than integrated to become one land use model in upper catchment by using computer program package âPoersim Version 2.5câ. The model is simulation by considering aspect land suitability, is then obtained by form land use sustainable. Land use in Cikapundung upper catchment equal to 70,52% disagree with land condition. The rate of occured erosion in dry land, pine forest and plantation of quinine have is abysmal of permissible erosion, while in natural forest, rice field, and grass land still is normal. Run off coefficient from all region per year go up equal to 0,3878%. And B/C dry land equal to 3,33. To maintain thickness of land and reducing runoff coefficient but admiting of to support lifeÂ  farmer, minimum 10% from rest of obtained production in using to defray activity of conservation. Crop vegetable type which still profit is potato, chickpea, and pepper so long as minimizing 5% from rest of obtained production to be used for the activity of conservation, appropriate action conservation type is credit terrace because can be done step by step every process farm so that farm can be exploited on an sustainable.